Drying Shrinkage and Mechanical Strength of Cementitious Composites with Alkali-Treated Makino Bamboo Fibers - Chin-Hao Yeh; Jyh-Horng Wu; Teng-Chun Yang (Journal of Natural Fibers)
Alkali-treated bamboo fibers (AFs) treated with different NaOH concentrations (5 and 10%) and treatment times (1, 12, and 24 h) were used as fillers to fabricate cementitious composites with AFs (CAFs) in the present study. The results demonstrated that alkali treatment caused the partial decomposition of hemicellulose and lignin and an increase in the surface roughness of bamboo fibers. Additionally, the amounts of calcium hydroxide in alkali-treated CAFs were higher than in untreated CAFs, and they increased with increasing NaOH concentration and treatment time. For drying shrinkage (DS) under 75% relative humidity (RH), the DS values of the CAFs significantly decreased after adding AFs compared to the DS values of untreated CAFs. Compared to untreated CAFs, the density of the 5% and 10% NaOH-treated CAFs with longer treatment times decreased by 2.9% and 5.1%, respectively. Furthermore, the tensile strength of all alkali-treated CAFs exhibited no significant differences when compared with that of untreated CAFs, while the modulus of rupture and compressive strength were significantly decreased by NaOH treatment. These results indicated that the AFs significantly improved the drying shrinkage of the CAFs and hydration retardation effect of cement pastes, while the density and mechanical strength of the CAFs decreased.